A conducting domain surface boundary applied to hybrid FEM-FDTD Electromagnetic models - Alias, R.; Abd-Alhameed, R. A.; Excell, P. S. (SAI Organization, 2012)
A modified boundary surface between the two domains in the hybrid FEM-FDTD technique is presented. This permits a heterogeneous surface to be imposed, allowing selected parts to be represented as being conducting or non-conducting. This enables a reduced surface size to be used in cases where an antenna is above a conducting plane, as well as facilitating a range of other practical scenarios. Examples presented show stable results and good agreement with published data.